Redox-Active Molecules as Therapeutic Agents - Fernandes, Ana Sofia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Oxidative stress and altered redox signaling have been described in a plethora of pathological conditions. Redox-active molecules can thus potentially be used to modulate the etiology/progression of such diseases. Recent advances in molecular biology and pharmacology have strengthened this area of research by providing novel mechanistic insights. This book compiles a collection of 13 articles, covering a range of topics from in vitro studies to clinical research, focused on the potential therapeutic effects of either natural or synthetic compounds, applicable to different redox-related diseases.